A Versatile Approach to Create Nanobubbles on Arbitrary Two‐Dimensional Materials for Imaging Exciton Localization. Issue 30 (12th September 2022) - Chen, Yulong; Song, Penghui; Wang, Chen; Zhang, Miao; Hu, Kaiming; Tian, Ziao; Su, Weitao; Chu, Paul K.; Zhang, Wenming; Di, Zengfeng
Abstract: Strained 2D materials with lattice deformation have the optimal band structure, lattice vibration, and thermal conductivity and various methods have been proposed to introduce strain into 2D materials. However, the creation of localized strain in arbitrary 2D materials in predesigned areas is difficult and challenging. Herein, a versatile approach to creating on‐demand nanobubbles on five different 2D materials using a functional atomic force microscopy (AFM) tip is described. Strain‐induced redshifts are observed from the Raman scattering and photoluminescence (PL) spectra of the 2D materials in the region with the nanobubble arrays. In addition, the localized exciton state is observed from the periphery of a steep WS2 nanobubble by high‐resolution nano‐photoluminescence and is supported by theoretical simulation. These results demonstrate a programmable and reliable method to create localized strain in different 2D materials and pave the way for nanoscale strain engineering of 2D materials to cater to different applications. Abstract : A versatile approach to realizing on‐demand nanobubbles on arbitrary 2D materials has been developed. Rendered by the accuracy of atomic force microscopy tip, an array of hundreds of 2D material nanobubbles can be obtained. Moreover, a localized exciton state is observed at the periphery of a steep WS2 nanobubble.